Enteroendocrine profile of α-transducin and α-gustducin immunoreactive cells in the chicken (Gallus domesticus) gastrointestinal tract. (28th June 2018) - Mazzoni, M; Karunaratne, T B; Sirri, F; Petracci, M; De Giorgio, R; Sternini, C; Clavenzani, P
ABSTRACT: The enteroendocrine profile and distribution patterns of the taste signaling molecules, α-gustducin (Gαgust ) and α-transducin (Gαtran ) protein subunits, were studied in the gastrointestinal (GI) tract of the chicken ( Gallus domesticus ) using double labeling immunohistochemistry. Gαtran or Gαgust immunoreactivity was observed in enteroendocrine cells (EEC) expressing different peptides throughout the entire GI tract with different density. In the proventriculus tubular gland, Gαtran or Gαgust /gastrin (GAS) immunoreactive (-IR) cells were more abundant than Gαtran/ or Gαgust containing glucagon-like peptide-1 (GLP-1) or peptide YY (PYY), whereas only few Gαtran or Gαgust cells co-stored ghrelin (GHR) or 5-hydroxytryptamine (5-HT). In the pyloric mucosa, many Gαtran or Gαgust -IR cells co-expressed GAS or GHR, with less Gαtran or Gαgust cells containing GLP-1, PYY, or 5-HT. In the small intestine, a considerable subset of Gαtran or Gαgust -IR cells co-expressed 5-HT in the villi of the duodenum and ileum, PYY in the villi of the jejunum, CCK or GLP-1 in the villi of the ileum, and GHR in the duodenum crypts. In the large intestine, many Gαtran or Gαgust -IR cells contained 5-HT or GLP-1 in the villi of the rectum, whereas some Gαtran /Gαgust -IR cells co-expressed PYY- or CCK-, and few Gαtran /Gαgust -IR cells were positive for GHR-IR. In the cecum, several Gαtran or Gαgust -IR cells were IR for 5-HT. Finally, many Gαtran /Gαgust cells containing 5-HT were observed in the villi and crypts of the cloaca, whereas there were few Gαtran or Gαgust /CCK-IR cells. The demonstration that Gα-subunits are expressed in the chicken GI enteroendocrine system supports the involvement of taste signaling machinery in the chicken chemosensing processes.